Sceptical theism undermines the fine-tuning argument. Mostly - Donahue, Miles K. (Religious studies, 2026)
After outlining sceptical theism (ST) and the fine-tuning argument (FTA), I demonstrate how arguments for the former undercut the latter. I then consider and reject three recent proposals for ameliorating the conflict: positive ST, considerations about normative superiors, and appeal to theistic metaethics. I contend, however, that Kirk Durston’s complexity argument for ST does not undercut the FTA but in fact supports it. In defending that thesis, I respond to Climenhaga’s contention that ST undermines all warrant for theistic belief, the FTA included.